Women's Work and Chicano Families Cannery Workers of the Santa Clara Valley - Zavella, Patricia (Cornell University Press, 1987)
At the time Women's Work and Chicano Families: Cannery Workers of the Santa Clara Valley was published, little research had been done on the relationship between the wage labor and household labor of Mexican American women. Drawing on revisionist social theories relating to Chicano family structure as well as on feminist theory, Patricia Zavella paints a compelling picture of the Chicano women who worked in northern California's fruit and vegetable canneries. Her book combines social history, shop floor ethnography, and in-depth interviews to explore the links between Chicano family life and gender inequality in the labor market.